De-radicalization Efforts Through Religious Moderation for State Islamic University of Raden Fatah Palembang Students - Muhamad Fauzi; Rohmadi Rohmadi (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2022)
Prejudice and claims of university as center of radicalism seeds appeared, after The National Counterterrorism Agency (BNPT) released that it was successful to create